Synthesis, Application and Effect of Hybrid Nanocomposites Based on Hydrogel and Nanoclay in Cement-Mortars - Watanuki Filho, Adhemar (2022)
Hybrid nanocomposite hydrogels, as admixtures for internal curing of cementitious materials, have been widely studied. This study analyzes the effect of applying 0.5% (wt/wt cement) of pre-soaked hydrogels based on polyacrylamide, carboxymethylcellulose, and three different concentrations of Cloisite-Na+ (0, 10, and 20% wt/wt) on the fresh and hardened properties of cementitious mortars. In general, all mortars with hydrogel decreased the consistency index, mainly M20, due to the high concentration of Cloisite-Na+ that modifies the release kinect of the hydrogel. The results showed a slight variation, with an overall average value of 99% water retention in all mortars. This behavior is due to the portion of hydrogel-mortars dosage water retained to reduce the availability of free water in the mixture because this amount of water is stored, a priori, within the polymer particles. At 28 d, the mortars produced with hydrogels containing 20% of nanoclay (M20) exhibit mechanical behavior similar to the reference mortar (M), which corroborates the percentage of voids found. Scanning electron microscope images confirm that the M and M20 mortars are uniform and possess few pores or microcracks. Thus, these hybrid hydrogels have the potential to be innovative materials for water control improvements in cementitious materials technology.